How Can We Do Better? Learning From 617 Pediatric Patients With Airway Foreign Bodies Over a 2-Year Period in an Asian Population - Gao, Ying-Qin; Tan, Jian Li; Wang, Mei-Lan; Ma, Jing; Guo, Jia Xi; Lin, Ken; Wei, Jing-Juan; Wang, De-Yun; Zhang, Tie-Song (Frontiers in Pediatrics, 2020)
Background Foreign body (FB) in the paediatric airway is a prevailing and crucial emergency with presenting symptoms often overlapping with other common paediatric conditions. There are no large cohort studies in an Asian population which demonstrate the diversity of symptoms, investigations which will aid in clinching the diagnosis, and definitive management. Cultural differences in an Asian society may also influence the presentation and type of paediatric airway FB. Methods This is a retrospective study of all airway FB treated in Kunming Children’s Hospital, China from February 2016 to June 2019. Results A total of 617 patients were included in our study. The age ranged from 4 months to 12 years (mean = 1.74 years). The duration of symptoms ranged from 1 hour to 605 days, with the diagnosis established at an average 9.16 days. Almost all had multiple symptoms, most commonly cough (98.5%) followed by noisy breathing (98.2%). 95.5 % of the FBs were organic and the rest inorganic. Of the organic FBs, peanut was the most common (31.6%), followed by walnut (13.3%) and sunflower seeds (9.2%). 80.8% of the organic FBs were incomplete while 85.7% of the inorganic FBs were completely intact. 43.3% of the patients had multiple FBs with 2.4% of them in different locations. Conclusions Airway FB can be easily missed with resultant delay in diagnosis. In an Asian population, walnut and sunflower/pumpkin seeds feature more prominently compared to Western populations. Sunflower seed FBs tend to present earlier and are found intact in the trachea. Rigid bronchoscopy is the most common technique used to remove such FBs and pulmonary-related complications post-operatively, though rare, are the most common adverse outcomes. Preventive strategies targeting the appropriate age group and this type of FB may be useful in an Asian population. Key words Paediatric, foreign body, chest radiography, bronchoscopy